Fair weather friends ; Lampang Kerubin ; Unconquerables [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Friendship between the Filipinos and Americans in Olongapo City was affected when they refused to allow passage in Subic during the Pinatubo eruptions; A film about mentally handicapped children and of Randy Zialcita who played Julius in the film; Mephenaij Pheton Youth Club, a group of youth who choose Apahan, Leyte to improve their community.